O uso do ERP (enterprise resource planning) e seu impacto na gestão de suprimentos em empresas da indústria de alimentos processados - Souza, Ludmila Cerqueira (2005)
In the past two decades, the manufacture companies have been faced significant changes in their business area, and the most evident and important was occurred in productive, organizational, technological and financial forms. The configuration of this new scenario demanded of the companies the capacity to modify its operational and productive concepts, in order to survive in an environment of high competitive pressure. In this context, importance of the use of tools is distinguished it that assist and speed the decision making, contributing for the increase of the competitiveness of the company. So, it is convenient that these tools make possible the complete access to information in all the parts and for all in the company, as the proposal of the ERP (enterprise resource planning) systems. The effective use of this system allows the company to integrate its managerial process in different internal functions, providing to productive improvement, minimizing waste and costs in the production process. Parallel, as a second factor comes gaining importance in the companies is the supply management. Forty to sixty per cent of the sale value of the non durable products is related to raw materials. Therefore, a relatively little cost reductions in the acquisition of materials can give a great impact on the company s profit. The objective of this research is to verify how the use of ERP helps the supply management in food industry companies that use sugar as a raw material. The carried through research is of qualitative nature, where a bibliographical survey on the subjects was elaborated, supply management, ERP systems and food industry, followed by explanatory case studies in three companies of food industry in the São Paulo State. It can be concluded that the ERP supports the operational and managerial activities related to supply management in the researched companies, mainly when the company consider the purchase function as a competitive resource. It was observed, however, that its functionalities aren t totally used by the researched companies.